Identification of Bacterial Surface Antigens by Screening Peptide Phage Libraries Using Whole Bacteria Cell-Purified Antisera - Hu, Yun-Fei; Zhao, Dun; Yu, Xing-Long; Hu, Yu-Li; Li, Run-Cheng; Ge, Meng; Xu, Tian-Qi; Liu, Xiao-Bo; Liao, Hua-Yuan (Frontiers in Microbiology, 2017)
Bacterial surface proteins can be good vaccine candidates. In the present study, we used polyclonal antibodies purified with intact Erysipelothrix rhusiopthiae to screen phage-displayed random dodecapeptide and loop-constrained heptapeptide libraries, which led to the identification of mimotopes. Homology search of the mimotope sequences against Erysipelothrix rhusiopthiae-encoded ORF sequences revealed 14 new antigens that may localize on the surface of Erysipelothrix rhusiopthiae. When these putative surface proteins were used to immunize mice, 9/11 antigens induced protective immunity. Thus, we have demonstrated that a combination of using the whole bacterial cells to purify antibodies and using the phage-displayed peptide libraries to determine the antigen specificities of the antibodies can lead to the discovery of novel bacterial surface antigens. This can be a general approach for identifying surface antigens for other bacterial species.